Did the 'Be Clear on Bowel Cancer' public awareness campaign pilot result in a higher rate of cancer detection?. Issue 1053 (9th April 2013) - Bethune, Rob; Marshall, Morwena J; Mitchell, Stephen J; Oppong, Chris; Cartmel, Mark T; Arumugam, Ponnandai J; Gee, Andrew S; Daniels, Ian R
Abstract : Objectives: To assess the impact of a 7-week public bowel cancer awareness campaign pilot by reviewing the number of 2-week referrals from general practitioners (GPs) to hospital, endoscopic procedures and new cancers diagnosed throughout the five acute hospitals in The Peninsular Cancer Network, UK. Design: A retrospective before and after study. Setting: The Peninsula Cancer Network in the South West of England, UK. Main outcome measures: For the period July 2010–July 2011, data were collected on the number of 2-week referrals, number of endoscopic procedures performed and number of new cancers diagnosed. The average for the 6 months before the campaign was compared with the immediate 3 months and then the fourth to sixth months following the campaign. Student's t test was used to compare the means of the three groups. Results: There was a statistically significant increase in the number of 2-week referrals from GPs to hospital in the 3 months following the campaign but this effect disappeared after that. There was no statistical increase in the number of endoscopic procedures or new cancers diagnosed following the awareness campaign. Conclusions: The pilot 'Be Clear on Cancer' awareness campaign had a significant effect on the number of patients being referred from GPs to hospital; however, the effect was short lived and had returned to baseline by 3 months. The campaign had no effect on the number of new cancers diagnosed, which was the stated underlying aim of the pilot.